Long-term land cover changes and ecosystem services variation: Have the anthropogenic transformations degraded human well-being in Italy? - Davide Marino; Margherita Palmieri; Angelo Marucci; Silvia Pili (Italian Review of Agricultural Economics (REA), 2022)
Landscape composition has a crucial role in determining ecosystem functioning and human well-being. Human activities (e.g. urban expansion or agricultural intensification) have strongly modified the natural environment and ecosystem integrity. This paper presents an exemplary application of the ecosystem service (ES) concept to the whole Italian territory. A GIS-based analysis of the long-term dynamics (1960-2018) between land cover changes and landscapes' capacities to provide ecosystem services was conducted in order to achieve a qualitative and quantitative assessment of the supply and demand of ES. The applied methodology considers a matrix linking spatially explicit biophysical landscape units to ecosystem services supply, which was united in a GIS framework. We set the analysis considering national scales and 3 time periods (1960-1990, 1990-2018, 1960-2018). As main results we found a great impact of intensification and urbanization on the decline of ES supply, while forest expansion and forest permanence determined the most important increases. The analysis detected several variations of ES supply that have direct impact on humans and can provide information about the importance of preserving the environment and the benefits we derive from nature.
Keywords: Q57; 330; ecosystem services; land cover changes; national scale assessment; GIS analysis